2022
DOI: 10.3390/toxins15010029
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA Treatment in Chronic Migraine: Investigation of Its Effects on Disability, Headache and Neck Pain Intensity

Abstract: Neck disability and pain are frequently encountered problems in patients with chronic migraine (CM). The long-term stimuli of neurons in the trigeminocervical junction may explain this situation. OnabotulinumtoxinA (ONA) treatment is one of the proven treatments for CM; however, there is no study data on the efficacy of ONA treatment on neck disability and pain in CM patients. Therefore, we aimed to investigate the effect of ONA treatment on disability, neck pain and headache intensity in CM patients. One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Considering the neck areas where OnabotulinumtoxinA treatment is applied, it is seen that it provides improvements in neck pain and disability, which are complaints of chronic migraine patients. In a hospital-based study, OnabotulinumtoxinA treatment was found to be effective for 3 months in reducing the intensity of NP, neck disability, intensity of headache, and number of monthly headache days and increasing the quality of life associated with CM [ 27 ]. The results of a systematic review reported that OnabotulinumtoxinA treatment in migraine was effective in reducing disability, headache intensity, frequency, and number of monthly headache days [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the neck areas where OnabotulinumtoxinA treatment is applied, it is seen that it provides improvements in neck pain and disability, which are complaints of chronic migraine patients. In a hospital-based study, OnabotulinumtoxinA treatment was found to be effective for 3 months in reducing the intensity of NP, neck disability, intensity of headache, and number of monthly headache days and increasing the quality of life associated with CM [ 27 ]. The results of a systematic review reported that OnabotulinumtoxinA treatment in migraine was effective in reducing disability, headache intensity, frequency, and number of monthly headache days [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study using this algorithm, neck and headache intensity, neck disability, and migraine disability decreased significantly in the third month after OnabotulinumtoxinA application in CM patients. In addition, the number of monthly headache days decreased from 20 to 6 [ 27 ]. Investigating the effects of the methods used in the treatment of CM on NP or disability, the intensity of headache, and the number of headache days per month will be useful for clinicians and researchers in predicting the patient’s condition.…”
Section: Introductionmentioning
confidence: 99%